2020
DOI: 10.1016/j.celrep.2020.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Division and Adaptation to Host Environment of Apicomplexan Parasites Depend on Apicoplast Lipid Metabolic Plasticity and Host Organelle Remodeling

Abstract: Highlights d Knockout of apicoplast TgATS2 disrupts LPA/PA for DrpC recruitment during cytokinesis d T. gondii can sense host environment and adapt to low host nutritional content d Under lipid starvation, parasite FASII and other lipid metabolic genes become essential d Upon nutrient deprivation, T. gondii induces host organelle remodeling and vesiculation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(123 citation statements)
references
References 66 publications
6
113
1
Order By: Relevance
“…Perhaps TgGC is able to move lipids between the apical cap and the Golgi, maybe in trafficking/signalling of phosphatidylinositol/PIPs? Interestingly, the PA examined in this study has a much higher presence of PA 18:1 than previous studies (Amiar et al 2020) and it might be because the parasites examined here are extracellular. The increase in PA might therefore have more 18:1 in extracellular parasites and more 18:0 in intracellular parasites, and this will be an interesting topic for future research.…”
Section: Tggc Likely Regulates the Pi Cyclecontrasting
confidence: 66%
See 1 more Smart Citation
“…Perhaps TgGC is able to move lipids between the apical cap and the Golgi, maybe in trafficking/signalling of phosphatidylinositol/PIPs? Interestingly, the PA examined in this study has a much higher presence of PA 18:1 than previous studies (Amiar et al 2020) and it might be because the parasites examined here are extracellular. The increase in PA might therefore have more 18:1 in extracellular parasites and more 18:0 in intracellular parasites, and this will be an interesting topic for future research.…”
Section: Tggc Likely Regulates the Pi Cyclecontrasting
confidence: 66%
“…The presence of a phospholipid transporter ATPase domain in TgGC is still ambiguous and we hypothesized that TgGC might have roles in lipid uptake, possibly via the host cell. To test whether TgGC has a role in nutrient (specifically lipid) uptake, we grew an ATc regulated TgGC inducible knockdown mutant (Yang et al 2019) with and without ATcin variable serum conditions to see if TgGC-depleted parasites could be rescued in a lipid rich environment, as has been shown in other mutants involved in phospholipid metabolism (Amiar et al 2020). Interestingly, we found that this growth defect could not be rescued by growing parasites in excess serum (FIgure 1B).…”
Section: Tggc Has a Dynamic Localizationmentioning
confidence: 80%
“…Our quantitative proteomic analysis shows potential compensatory mechanisms may be used by the parasites in response this early perturbation of the apicoplast lipid metabolism that precedes organelle loss. Tachyzoites are indeed known to be able to use exogenous lipid sources to adapt metabolically (86, 87), and interestingly upon depletion of TgSufS we observed a pattern of overexpression for ER-located enzymes involved in the synthesis of several phospholipids and ceramides (Table S3). These lipids are usually synthesized in the ER from apicoplast-synthesized precursors, but this may clearly indicate a compensatory mechanism that would make use of precursors scavenged form the host instead.…”
Section: Discussionmentioning
confidence: 86%
“…Dissecting how the flippase SNPs modulate the kinetics or substrate preference will require extensive further work. A string of recent insights supports the role of the FASII pathway in in vitro virulence [5760]. Furthermore, the availability of lipids in the extracellular environment has been identified as a critical factor for in vitro virulence in a dose-dependent manner [57, 61].…”
Section: Discussionmentioning
confidence: 99%